ANALISA PERBEDAAN CITRA DESTINASI PENDUDUK LOKAL DAN WISATAWAN, DAN IMPLIKASINYA BAGI PEMASARAN WISATA JAKARTA - Budi Budi (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
Destination image is an important factor in tourism marketing. Harmonious destination image between local residents, tourists, and Tourism Marketers Organization allows for a sustainable development model for tourism marketing. This study aims to examine differences of Jakarta's destination image in the perception of tourists and local residents. Methodology used is quantitative research. Research instruments are developed by reviewing relevant literature on destination image factors for Jakarta. Data collection is done through questionnaires distributed online. Different test conducted is Mann-Whitney test. Results show that local residents and tourists have similar destination image about culinary tourism and shopping. But they have different destination image about recreation, cultural tourism, beach tourism, historical tours, local people, infrastructure, affective destination image, and conative destination image. Researcher suggested to Tourism Marketers and Tourism Department of Jakarta to educate, to give information, and to involve local people especially to destination images that still considered low by local residents. Tourism Marketer Organizations, Jakarta Tourism Office, and Local Residents must maintain and even improve the quality of culinary tour and shopping experience so as to increase the satisfaction of tourists when visiting Jakarta, which in turn will make tourists want to re-visit.